Spontaneous subdural haemorrhage in a patient with scleroderma renal crisis. (5th September 2014) - Bhangoo, Munveer Singh; Hein, Paul; Nicholson, Laura; Carter, Caitlin
Abstract : A 52-year-old woman with a history of systemic sclerosis presented with new onset seizures and renal failure. The patient's history, laboratory data and pathology supported the diagnosis of scleroderma renal crisis. The patient was also noted to have a subdural haemorrhage (SDH) in the absence of trauma. This is the first report of scleroderma renal crisis associated with a spontaneous SDH.